'Father, father, where are you going?': Epicurean Deism and Absent Fathers in Blake's Songs of Innocence and of Experience. (13th September 2019) - Codsi, Stephanie
Abstract: This article explores the connection between the absent deity of Epicurean Deism and the father figure in Blake's Songs of Innocence and of Experience (1789–1794). The absent, elusive or indifferent God – which I trace back to Epicurean theology and its theory of atoms – plays out in Blake's depiction of a father whose absence or neglect is an implied cause of man's alienation. The article firstly looks at the inheritance of Epicureanism in 17–18th century Deist texts, then considers Blake s references to Epicureanism in his works, and finally argues that Blake critiques such concepts of God and fatherhood in a selection of Songs .